An open-label extension study to demonstrate long-term safety and efficacy of ABP 501 in patients with rheumatoid arthritis - Cohen, Stanley; Pablos, Jose L; Pavelka, Karel; Müller, Gerard Anton; Matsumoto, Alan; Kivitz, Alan; Wang, Hui; Krishnan, Eswar (Arthritis research & therapy, 2019)
BACKGROUND: ABP 501 was evaluated in a phase 3 single-arm, open-label extension (OLE) study to collect additional safety and efficacy data in patients with rheumatoid arthritis (RA). METHODS: Subjects completing the final visit in the parent phase 3 randomized, double-blind, controlled equivalence study comparing the efficacy and safety of the biosimilar ABP 501 with adalimumab reference product (RP) were enrolled in this open-label extension (OLE) study. All subjects received 40 mg ABP 501 every other week for 68 weeks. Key safety endpoints included treatment-emergent adverse events (TEAEs), serious adverse events (SAEs), and anti-drug antibody (ADA) incidences. Efficacy endpoints included ACR20 (at least 20% improvement in American College of Rheumatology core set measurements from baseline) and Disease Activity Score 28-joint count C-reactive protein (DAS28-CRP) change from baseline. RESULTS: Among 466/467 patients treated with ABP 501, 229 transitioned from the ABP 501 arm of the parent study (ABP 501/ABP 501) and 237 from the adalimumab RP arm (RP/ABP 501); 412/467 (88.2%) patients completed the study. The overall TEAE incidence was 63.7% (297/466); grade ≥ 3 TEAE incidence was 9.0% (42/466). The incidence of TEAEs leading to discontinuation of investigational product was 3.6% (17/466). The SAE incidence was 9.9% (46/466). Overall, 18.2% (85/466) of subjects developed binding ADAs and 6.9% (32/466) developed neutralizing ADAs in the OLE study. The ACR20 response rate was 73.3% (340/464 subjects) at OLE baseline, and 78.8% (327/415 subjects) at week 70 of the OLE study. The overall mean DAS28-CRP change from the parent study baseline was - 2.25 at the OLE study baseline (n = 440), - 2.36 at week 4 (n = 463), - 2.41 at week 24 (n = 450), - 2.55 at week 48 (n = 433), and - 2.60 at week 70 (n = 412). Efficacy was maintained throughout the study. CONCLUSIONS: Efficacy previously demonstrated in the parent study was maintained in this OLE study with no new safety findings. Long-term safety, immunogenicity, and efficacy were similar in the ABP 501/ABP 501 and RP/ABP 501 groups. The single switch from RP to ABP 501 did not impact immunogenicity. TRIAL REGISTRATION: ClinicalTrial.gov, NCT02114931.
Keywords: rozvrh dávkování léků; ABP 501; dospělí; Nasopharyngitis; Biosimilar Pharmaceuticals; Arthritis, Rheumatoid; Female; Biosimilar; Rheumatoid arthritis; revmatoidní artritida; Adult; výsledek terapie; ženské pohlaví; adalimumab; lidé; dvojitá slepá metoda; Drug Administration Schedule; Treatment Outcome; biosimilární léčivé přípravky; Efficacy; Double-Blind Method; Male; Long-term safety; Aged; Antirheumatic Agents; lidé středního věku; nazofaryngitida; senioři; mužské pohlaví; antirevmatika; Middle Aged; Adalimumab; Humans